Estudios morfológicos y taxonómicos en Digitaria Haller (Poaceae: Panicoideae: Paniceae): inventario y primer registro de Digitaria velutina (Forssk.) P. Beauv. para Sudamérica (2016)
As a result of recent studies on Neotropical grasses, a checklist of the South American species of Digitaria is provided. This checklist includes 65 species, of which 53 are native (34 are endemic) and 12 are introducednaturalized. Brazil has 48 species (12 endemic), followed by Venezuela (29/1), Paraguay (28/0), Colombia (27/2), Argentina (26/1), and Bolivia (24/1). On the other hand, D. velutina (Forssk.) P. Beauv., a native species from Africa, Arabia, and Yemen, is recorded for the first time in South America. This paper includes the morphological similarities and differences between D. velutina and D. abyssinica (Hochst. ex A. Rich.) Stapf. The names D. bonplandii Henrard and D. mattogrossensis (Pilg.) Henrard, are included in the synonymy of D. corynotricha (Hack.) Henrard.